2019
DOI: 10.1080/10926771.2018.1561572
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of a Psycho-Social Approach for Understanding and Addressing Male Youth Violence: The Interface between Traumatic Experiences and Masculinity

Abstract: The long-term relationship between Adverse Childhood Experiences (ACEs) such as exposure to violence in the home and in the community, healthharming behaviors, poor physical and mental health outcomes, and ultimately, early mortality was first documented by Felitti et al. (1998) in their seminal study with more 8,000 people in the United States. However, it is clear that not all people experience the same types of adversity (Grasso, Dierkhishing, Branson, Ford, & Lee, 2015) and even when they do, the behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…These findings complement those from previous studies (e.g. Milaniak and Widom, 2015) that have suggested that broad measures against adversity, specifically those limited to the family environment, reduce the understanding of causal factors that contribute to violent offending and the socio-emotional pathways that link trauma to violence (Walsh, 2020b). Similar associations have been found in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…These findings complement those from previous studies (e.g. Milaniak and Widom, 2015) that have suggested that broad measures against adversity, specifically those limited to the family environment, reduce the understanding of causal factors that contribute to violent offending and the socio-emotional pathways that link trauma to violence (Walsh, 2020b). Similar associations have been found in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…However, exposure to more frequent and intense adverse and traumatic experiences during early life is likely to negatively impact upon mental health (Cecil et al, 2017). A considerable body of evidence now indicates that there is a possible mediated association between early trauma, specifically violent victimisation, and violence perpetration later in life, particularly amongst males (Ellis, 2016;Ellis et al, 2017;Walsh, 2020;Winlow, 2014).…”
Section: A Ticking Time Bomb? Trauma Violence and Economic Hardshipmentioning
confidence: 99%
“…Similarly, De-Zulueta (2006: 5) has argued that memories of past abuse that are dissociated "can be processed into rage...when triggered by the appropriate stimuli". Whilst the underlying psychic mechanisms of trauma and violence are becoming better understood, there remains a need to acknowledge both the influence of gender, particularly masculinity, upon this association (Walsh, 2020) and traumatic abuse which can lead to forms of future violence. Numerous research studies indicate overwhelmingly that violence, particularly persistent and more harmful violence, is largely the preserve of males (Currie, 2016;Ellis, 2016;Winlow, 2014).…”
Section: A Ticking Time Bomb? Trauma Violence and Economic Hardshipmentioning
confidence: 99%
“…Women have been found to be at higher risk of clinical disorders such as PTSD, anxiety, depression, self-harm, eating disorders and emotionally unstable personality disor der, whereas men have been found to be at greater risk of behavioural difficulties , cognitive misinterpretations of risk, and increased aggression (DHSC, 2018; Wilton and Williams, 2019; Mental Health Foundation, 2017). These gendered responses to trauma are understood within the wider context of men's lives and the role of hegemonic masculinity (Walsh, 2020). For women who experience multiple disadvantage, trauma (such as violent trauma) can be a trigger into offending, substance use and/or homelessness, experiences which in turn cause further trauma which again is differentiated along gendered lines.…”
Section: The Role Of Gender Norms and Gender Inequalitymentioning
confidence: 99%